Jasmonic Acid Enhances Rice Cadmium Tolerance by Suppressing Cadmium Uptake and Translocation - Hao Zhang; Zhengkai Liu; Xinyu Li; Xiaodong Liu; Linzhi Fang; Rensen Zeng; Qiongli Wang; Yuanyuan Song; Daoqian Chen (Plants)
Worldwide, cadmium (Cd) contamination severely threatens rice production and public health. Jasmonic acid (JA) is recognized to be involved in rice Cd stress responses, but the underlying mechanism remains unclear. In this study, we show that JA positively regulates Cd tolerance in rice by repressing Cd uptake and root-to-shoot translocation. Cd exposure rapidly elevated the endogenous JA in rice roots, which was associated with increased expression of JA synthesis and JA-responsive genes. Moreover, silencing the expression of either allene oxide synthase (OsAOS; active in JA biosynthesis) or CORONATINE INSENSITIVE1 (OsCOI1; active in JA perception) resulted in aggravated Cd toxicity and increased Cd accumulation in both the roots and shoots, as well as increased translocation from the root to the shoots. A short-term uptake experiment revealed that silencing of OsAOS and OsCOI1 enhanced root Cd uptake ability. Furthermore, the elevated transcript levels of genes for Cd uptake (OsNramp5, OsNramp1, and OsIRT1) and root-to-shoot translocation (OsHMA2) were observed in OsAOS and OsCOI1 RNAi plants in comparison with wild-type plants. Taken together, our findings suggest that JA enhances rice cadmium tolerance by suppressing Cd uptake and translocation.